Development of greenhouse gas emissions baseline and identification of carbon offset cost for maritime vessels of a developing country - Semab, Basra; Iqbal, Kanwar Muhammad Javed; Amir, Sarah; Tariq, Muhammad Atiq Ur Rehman (Frontiers in Environmental Science, 2023)
Maritime transportation has drawn international attention due to the gradual rise and projected growth of GHG emissions resulting from fossil fuel consumption. It is alarming that the overall maritime transportation emissions are neither attended nor mainstreamed under the transportation sector. The actual national inventory of GHG emissions vis-à-vis all types/sizes of maritime vessels is so far not established particularly in developing countries, which clearly indicates the inadequacy of their climate mitigation response. Accurate assessment of GHGs is essential to provide reliable input for climate policy, strategies, and decision-making processes by flag states. Therefore, the establishment of a baseline reference scenario by considering all types / sizes of maritime vessels is crucial to know the actual gravity of the problem, which is still unknown. This entailed the need to explore the actual extent of GHG emissions from the maritime transportation sector. In this context, the present study tried to assess the potential GHG emissions from maritime vessels by undertaking the case of Pakistan and using the top-down approach, which took into account fuel consumption and emission factors for GHGs. It revealed that 2,468,789.21 tonnes of GHGs (CO2e) are being emitted annually from the maritime vessels of Pakistan, which is 4.9% of overall transport sector emissions of the country. Carbon offset cost of 37,031,838.14 US$/annum and approximately 20,020 hectares of mature mangrove forest to remove 2,468,789.21 metric tonnes of CO2e emissions from the atmosphere in a timeline of one year are required to become carbon neutral. It is anticipated that this study’s outcome will serve as a baseline reference scenario for national GHG inventory and help in devising climate mitigation response for maritime vessels by bridging the existing knowledge gap.